Antioxidative Role of Hatikana (Leea macrophylla Roxb.) Partially Improves the Hepatic Damage Induced by CCl4 in Wistar Albino Rats. (14th June 2015) - Akhter, Samina; Rahman, Md. Atiar; Aklima, Jannatul; Hasan, Md. Rakibul; Hasan Chowdhury, J. M. Kamirul
Abstract : This research investigated the protective role of Leea macrophylla extract on CCl4 -induced acute liver injury in rats. Different fractions of Leea macrophylla (Roxb.) crude extract were subjected to analysis for antioxidative effects. Rats were randomly divided into four groups as normal control, hepatic control, and reference control (silymarin) group and treatment group. Evaluations were made for the effects of the fractions on serum enzymes and biochemical parameters of CCl4 -induced albino rat. Histopathological screening was also performed to evaluate the changes of liver tissue before and after treatment. Different fractions of Leea macrophylla showed very potent 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging effect, FeCl3 reducing effect, superoxide scavenging effect, and iron chelating effect. Carbon tetrachloride induction increased the level of serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (ALP) and other biochemical parameters such as lipid profiles, total protein, and CK-MB. In contrast, treatment of Leea macrophylla reduced the serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (ALP) activities as well as biochemical parameters activities. L. macrophylla partially restored the lipid profiles, total protein, and CK-MB. Histopathology showed the treated liver towards restoration. Results evidenced that L. macrophylla can be prospective source of hepatic management in liver injury.